Spectrum of Slow and Super-Slow (Picosecond to Nanosecond) Water Dynamics around Organic and Biological Solutes - Ramakrishnan, Gopakumar; González-Jiménez, Mario; Lapthorn, Adrian J; Wynne, Klaas (The journal of physical chemistry letters, 2017)
Water dynamics in the solvation shell of solutes plays a very important role in the interaction of biomolecules and in chemical reaction dynamics. However, a selective spectroscopic study of the solvation shell is difficult because of the interference of the solute dynamics. Here we report on the observation of heavily slowed down water dynamics in the solvation shell of different solutes by measuring the low-frequency spectrum of solvation water, free from the contribution of the solute. A slowdown factor of ∼50 is observed even for relatively low concentrations of the solute. We go on to show that the effect can be generalized to different solutes including proteins.